STUDI LITERATUR TENTANG PENGARUH PENGGUNAAN DOMINO CARDS DALAM MENINGKATKAN KOSAKATA BAHASA INGGRIS SISWA SD - Era Fasira JR; Suwito Eko Pramono; Agus Yuwono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
ABSTRACT This research aims to determine the effect of using Domino Cards in increasing elementary school students' English vocabulary. Along with the rapid development of technology and new innovations, there are many teaching media that can be used to help teachers make learning more interesting and flexible. In this research, researchers used qualitative research methods. The data collection technique is in the form of literature study by reading several previously published scientific journal references. The research results showed that the use of domino cards had a positive impact on increasing students' mastery of English vocabulary. Thus, the use of domino cards as a teaching medium has proven to be effective in helping students improve their English vocabulary. This research suggests making clear instructions when applying teaching media such as the domino cards game so that it can make it easier for students in the learning process.